Corilagin: First Time Isolation from the Whole Plant of Phyllanthus maderaspatensis L. - Kochumadhavan, Abhilash; Mangal, Priyanka; Kumar, LM Sharath; Madhura Meenakshi, Badugu; Uddagiri Venkanna, Babu; Muguli, Ganesh (Asian Journal of Biological and Life Sciences)
Introduction: Corilagin, an ellagitannin (chemical name β-1-O-galloyl-3,6- (R)-hexahydroxydiphenoyl-d-glucose), was previously reported from other species of Phyllanthus except Phyllanthus maderaspatensis L. Therefore, the aim of the study was to isolate corilagin from P. maderaspatensis and report it as chemo-marker. Methods: The whole plant of P. maderaspatensis was subjected to hot extraction and partitioning, followed by repeated column chromatography (silica, Diaion HP-20 and Prep HPLC). The observed LC‑MS/MS and NMR data were compared with reported literature to verify the structure of the isolated molecule as corilagin. Results: The LC-MS/MS chromatogram showed a peak at retention time 22.05 min, with m/z 633 for [M - H]− along with characteristic major fragments at m/z 463 [M - 170 - H]− and m/z 301 [M - 332 - H]−. The NMR results were also in accordance with literature. Conclusion: This is the first report on isolation of corilagin from P. maderaspatensis whole plant for standardization and quality control of the plant.
Keywords: Phyllanthus maderaspatensis; Corilagin; Ellagitannin; 1H NMR and 13C NMR.